Design process of the Memorial Cathedral for World Peace (1954), Hiroshima, by Togo Murano (Part 3): Formal manipulations observed in the process of schematic design of the cathedral (1948) - Yoshito Tomioka; Chikako Tabata (Japan Architectural Review, 2024)
Abstract The collection of Kyoto Institute of Technology features numerous sketches and drawings scanning wide variety of exterior compositions of the cathedral. Togo Murano recalled that receiving the understanding and approval of the Fathers was challenging. This study analyzes the creative evolution of the cathedral's exterior form until the conclusion of the schematic design in November 1948. The proposed analytical method was applied to completely undated sketches and drawings to reveal the architect's morphological creation. Furthermore, it revealed the development of diverse types in an extremely short period, as well as the architect's design thinking and strategy in this phase.